APLIKASI CHEM DRAW SEBAGAI MEDIA INOVASI GURU DALAM PENGAJARAN IPA TERPADU - Rina Hidayati Pratiwi; Endang Suistyaningsih; Kevin Septianzah (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2019)
The teacher is one of person who determines successful in learning student at the school. Thus, the teacher is demanded giving some innovations of learning creatively to reach comprehension for the student. The aim of this study is to know the respond of each teacher for Chem Draw application that one of media for a teacher to innovate in integrated natural science learning. Chem Draw is one of application in Chem Office. Many teachers gave the good responses and showed enthusiasm while was given learning of Chem Draw application. The teacher showed innovation after was given that practice. Although Chem Draw is more use for senior high school about learning of chemistry than another student, Chem Draw that was given MI and MTs teacher is successful for teachers show innovation. Features and facilities from Chem Draw applications are used by a teacher more in media of natural science learning. They argued that features and facilities in Chem Draw application are not only for Chemistry but also for mathematics and another science. Thus, the teacher of natural science at MI and MTs were more imaginate by using Chem Draw application, with the result that all of their task can be finished as soon as easy.